2015
DOI: 10.1136/jech-2014-204667
|View full text |Cite
|
Sign up to set email alerts
|

Access to green space, physical activity and mental health: a twin study

Abstract: Background Increasing global urbanisation has resulted in a greater proportion of the world’s population becoming exposed to risk factors unique to urban areas, and understanding these effects on public health is essential. The aim of this study was to examine the association between access to green space and mental health among adult twin pairs. Methods We used a multilevel random intercept model of same-sex twin pairs (4338 individuals) from the community-based University of Washington Twin Registry to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
2
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(177 citation statements)
references
References 52 publications
7
156
2
12
Order By: Relevance
“…However, two other studies showed null findings [60, 61]. Similarly, while some research has shown a significant inverse association of exposure to neighborhood green space with multiple aspects of mental ill-health, such as depression, anxiety and stress [62], other research has found this association to be limited only to some but not other aspects of mental health [63]. Of note, the effect of parks on mental health may be more pronounced in low-income neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…However, two other studies showed null findings [60, 61]. Similarly, while some research has shown a significant inverse association of exposure to neighborhood green space with multiple aspects of mental ill-health, such as depression, anxiety and stress [62], other research has found this association to be limited only to some but not other aspects of mental health [63]. Of note, the effect of parks on mental health may be more pronounced in low-income neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in areas with higher levels of air pollution, people tend to reduce the amount of time they spend outdoors 12 . Such averting behavior introduces a number of indirect pathways through which air pollution may further induce or worsen psychological distress, including limited exposure to sunlight and subsequent vitamin D deficiency 13,14 , reduced physical activity and/or exercise 15,16,17 , reduced contact with parks and other green space 18,19,20 , and social isolation 21,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Park space is a crucial thread in the fabric of a community, providing benefits to health through mental rejuvenation (Salmond et al, 2016;Cohen-Cline, Turkheimer, & Duncan, 2015) and opportunities for active recreation (Niemela, 1999); a place for wildlife and vegetation to flourish (Toni & Duinker, 2015); a space that can absorb air pollution (Chang & Li, 2014); a booster of land value (Brambilla & Ronchi, 2016); and a wellspring of economic opportunity (Sander, 2016). Subsequently, allocating resources for the establishment of these spaces should be the priority of all municipalities; however, creating an effective park requires more than just spare land and political will.…”
Section: Literature Reviewmentioning
confidence: 99%